Microfluidic System to Analyze the Effects of Interleukin 6 on Lymphatic Breast Cancer Metastasis - Cho, Hyeon-Yeol; Choi, Jin-Ha; Kim, Kyeong-Jun; Shin, Minkyu; Choi, Jeong-Woo (Frontiers in Bioengineering and Biotechnology, 2021)
Metastasis is the primary cause of a large number of cancer-associated deaths. By portraying the precise environment of the metastasis process in vitro, the microfluidic system provides useful insights on the mechanisms underlying cancer cell migration, invasion, colonization, and the procurement of supplemental nutrients. However, current in vitro metastasis models are biased in studying blood vessel-based metastasis pathways and thus the understanding of lymphatic metastasis is limited which is also closely related to the inflammatory system. To understand the effects of inflammatory cytokines in lymphatic metastasis, we developed a three-channel microfluidic system by mimicking the lymph vessel-tissue-blood vessel (LTB) structure. Based on the LTB chip, we successfully confirmed the inflammatory cytokine, interleukin 6 (IL-6), -mediated intercellular communication in the tumor microenvironment during lymphatic metastasis. The IL-6 exposure to different subtypes of breast cancer cells was induced epithelial-mesenchymal transition (EMT) and improved tissue invasion property (8-fold). And the growth of human vein endothelial cells towards the lymph vessel channel was observed by VEGF secretion from human lymphatic endothelial cells with IL-6 treatment. The proposed LTB chip can be applied to analyze the intercellular communication during the lymphatic metastasis process and be a unique tool to understand the intercellular communication in the cancer microenvironment under various extracellular stimuli such as inflammatory cytokines, stromal reactions, hypoxia, and nutrient deficiency.